Pleiotropic Roles of CXCR4 in Wound Repair and Regeneration - Chen, Huating; Li, Gongchi; Liu, Yiqiong; Ji, Shuaifei; Li, Yan; Xiang, Jiangbing; Zhou, Laixian; Gao, Huanhuan; Zhang, Wenwen; Sun, Xiaoyan; Fu, Xiaobing; Li, Binghui (Frontiers in Immunology, 2021)
Wound healing is a multi-step process that includes multiple cellular events such as cell proliferation, cell adhesion, and chemotactic response as well as cell apoptosis. Accumulating studies have documented the significance of stromal cell-derived factor-1 (SDF-1)/C-X-C chemokine receptor 4 (CXCR4) signaling in wound repair and regeneration. However, the molecular mechanism of regeneration is not clear. This review describes various types of tissue regeneration that CXCR4 participates in and how the efficiency of regeneration is increased by CXCR4 overexpression. It emphasizes the pleiotropic effects of CXCR4 in regeneration. By delving into the specific molecular mechanisms of CXCR4, we hope to provide a theoretical basis for tissue engineering and future regenerative medicine.